On the Global Community of Shared Future for Mankind under the COVID-19 Epidemic - LIU, WENDIAN (Pacific International Journal, 2022)
The 18th National Congress of the Communist Party of China clearly put forward that "we should advocate Community of Shared Future for Mankind consciousness, take into account the reasonable concerns of other countries when pursuing our own interests, promote the common development of all countries while pursuing our own development, establish a more equal and balanced new global development partnership, help each other in the same boat, share the responsibilities and responsibilities, and promote the common interests of mankind". The 19th National Congress of the Communist Party of China also mentioned that "we call on people of all countries to make concerted efforts to build Community of Shared Future for Mankind and a world of lasting peace, universal security, common prosperity, openness, tolerance, cleanliness and beauty." Over the years, China has been working hard to promote the construction of Community of Shared Future for Mankind. In 2020, the COVID-19 epidemic ravaged the world. This epidemic is a mirror, which shows us the necessity of building Community of Shared Future for Mankind, the efforts made by China, and the difficulty of building Community of Shared Future for Mankind.